Outcome of universal life-long ART for all HIV infected pregnant and breastfeeding women and children less than 24 months regardless of WHO stage or CD4 count (PMTCT option B+) - a case study in a rural district, Malawi - Tsiku, Packson (Department of Paediatrics and Child Health, 2015)
Background: Malawi has one of the highest HIV/AIDS prevalence rates in sub-Sahara Africa. It has the ninth largest HIV burden in the world. Following the 2010 WHO PMTCT recommendations Malawi started providing lifelong ART to HIV-infected pregnant and lactating women regardless of clinical stage or CD4 count (option B+) in July 2011. Aim To assess the outcome of pregnant and lactating mothers receiving ART (option B+) and their infants less than 24 months in a rural health district of Malawi. Methods: A retrospective cohort study of option B+ women who were initiated on ART between 1st July 2011 and 31st December 2012 was conducted in Ntchisi district. Their exposed infants were also enrolled in the study. The study participants were followed up to 31st December 2013. Data was mainly collected from ART registers, ANC registers and ART patient master cards using structured questionnaires. Data analysis was done using Microsoft Excel and Statistical Package for Social Science (SPSS). Results: A total of 201 option B+ mothers, 136 pregnant women and 65 lactating mothers were enrolled in our study. Their median age was 32 years. 19.9% of HIV pregnant mothers started ANC at less than 12 weeks gestation and 21% attended the recommended four ANC visits or more. The proportion of pregnant and lactating women tested for HIV was 89.6%. Uptake of ART in HIV positive pregnant and lactating women was 80.1%. Of 54 option B+ mothers enrolled in the July 2011-December 2011 cohort, 70.4%, 64.8%, 57.4% and 55.6 % were retained at 3, 6, 12 and 24 months respectively, and 73.5%, 66% and 65.3% of 147 option B+ mother enrolled in the January 2012-December 2012 cohort were retained at 3, 6 and 12 months respectively. Out of 126 option B+ who remained in care in December 2013, 89 (70.6%) had adherence rate of 95% or more in the last visit of the October-December 2013 quarter. Of all women who commenced option B+ during pregnancy, 56/ 77 (72.7%) who remained in care during the October-December 2013 quarter had adherence of at least 95%, while 33/49 (67.3%) of women who commenced option B+ during lactation and who remained in care during the October - Dec ember 2013 quarter had adherence of at least 95% or more. This difference was not statistically significant, OR = 1.2, 95% CI: 0.6-2.8. A total of 198 exposed infants were enrolled and their median birth weight was 3.2 kg. Uptake of PCR/rapid test for the infants was 73.7 %. 163/198 (82.3%) received NVP. Out of 53 exposed infants enrolled in Jul y 2011-Dec ember 2011 birth cohort, 81.1 %, 67.9 %, 5 1 % and 17 % were retained at 3, 6, 12 and 24 months respectively. In the January 2012-Dec ember 2012 cohort the proportion of exposed infant s retained were 89 %, 81.2 % and 47.6 % at 3, 6 and 12 months respectively. Of all infants tested for HIV infection during the study period, a higher proportion who were enrolled in the July-Dec ember 2011 birth cohort became HIV-infected compared to those enrolled in the January-December 2012 cohort, 7/ 3 4 ( 20. 6 %) versus 4/ 112 ( 3.6 %), OR = 7.0, 95% CI: 1.9 -25.7. A significantly higher proportion of HIV-exposed infants born to mothers who initiated ART during lactation acquired HIV infection than those born to mothers who initiated ART during pregnancy, 7/43 (16.3%) versus 4/103 (3.9%), OR = 4.8, 95% CI: 1.3 - 17.4. Conclusion: Our research findings suggest that the PMTCT programme in the Ntchisi district can be improved. Late booking during pregnancy, initiation of ART late during pregnancy or only during lactation, low retention in care for HIV pregnant and lactating mothers and their HIV-exposed infants, inadequate HIV testing of HIV-exposed infants and low ART adherence rate of HIV pregnant and lactating mothers should be addressed in order to optimize the administration and effectiveness of option B+.